2003
DOI: 10.1016/s0960-9822(03)00263-x
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Reason for a Big Difference

Abstract: The present investigations were undertaken to compare interspecific communicative abilities of dogs and wolves, which were socialized to humans at comparable levels. The first study demonstrated that socialized wolves were able to locate the place of hidden food indicated by the touching and, to some extent, pointing cues provided by the familiar human experimenter, but their performance remained inferior to that of dogs. In the second study, we have found that, after undergoing training to solve a simple mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
293
3
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 603 publications
(316 citation statements)
references
References 16 publications
17
293
3
3
Order By: Relevance
“…Since the direction of this trend was the same for wolves and for domestic dogs, both might be said to share this predisposition. This is contrary to previous suggestions that dogs, but not wolves, have been prepared to look at human faces through the process of domestication (Miklósi et al, 2003). However, such a predisposition toward attentive individuals would not explain why different groups of canids differed in success based on the types of occluder utilized in Experiment 1 or in previous experiments of this type (Cooper et al, 2003;Gácsi et al, 2004).…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Since the direction of this trend was the same for wolves and for domestic dogs, both might be said to share this predisposition. This is contrary to previous suggestions that dogs, but not wolves, have been prepared to look at human faces through the process of domestication (Miklósi et al, 2003). However, such a predisposition toward attentive individuals would not explain why different groups of canids differed in success based on the types of occluder utilized in Experiment 1 or in previous experiments of this type (Cooper et al, 2003;Gácsi et al, 2004).…”
Section: Discussioncontrasting
confidence: 84%
“…If it is true that "the unusual skills of domestic dogs in using human communicative cues most likely evolved during and as a result of human domestication" (Hare et al, 2010, p. E6), then all healthy populations of domestic dogs should be expected to outperform nondomesticated canids on human attentionalstate tasks. Furthermore, this should hold true independent of the age, condition, home environment, or experience level of the dog under test (Hare et al, 2002;Miklósi et al, 2003;Riedel et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of dogs the head direction of humans seemed to be more important than the gaze, when comparing the performance of guide dogs of blind owners to pet dogs of sighted owners (Gaunet 2008;Ittyerah and Gaunet 2009). Furthermore, some studies showed wolves to be inferior (Hare et al 2002;Miklósi et al 2003;Virányi et al 2008) and others superior (Udell et al 2008) to dogs in their ability to read human cues and recognise their state of attention. Dogs may have inherited the ability to read human given cues from wolves through a process of selection and convergent evolution or, as in chimpanzees, may have gained it through socialization to humans and training (Hare et al 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Some dogs brought the object to the front of the person even when they were facing away, and they begged from the person facing them in preference to the person facing away Virányi et al 2004). Such tasks have been determined to be cooperative in nature (Hare 2001), and especially domestic species have been bred for cooperativeness with humans (Gácsi et al 2005;Miklósi et al 2003). The domestication theory has been supported by the fact that cooperatively working dog breeds outperformed independently working breeds in such tasks (Gácsi et al 2009a).…”
Section: Introductionmentioning
confidence: 99%